A comparative study between the traditional Bajau communities and the existing Bajau communities in Davao City and its relationship towards the sense of community in existing Bajau communities - Dela Plaza, Micah Angelou R.; Olalo, Kristin Faye M. (2018)
The research evaluated the characteristics of traditional Bajau communities that existed before 1980 and the existing Bajau communities in Davao city in the year 2017 focusing on the physical environment, human activities, and culture. The study aims to identify the characteristics of the traditional and existing Bajau communities and how these characteristics have retained and changed after 40 years. The research gathered information and illustrations from the published literature for the traditional Bajau communities and conducted on-site photo-documentation and evaluation for the two existing Bajau communities in Davao city namely the Badjao Association in Matina Aplaya and St. John Badjao Community in Bucana. Furthermore, in-depth interviews involving Bajaus of different ages were conducted to evaluate the sense of community in existing Bajau communities and to further assess the communities? characteristics and their relationship with those of traditional Bajau communities. The data gathered from the research were analysed through descriptive comparative analysis wherein the result showed that for almost 40 years, the existing Bajau communities in Davao city had significant differences from the traditional Bajau communities that existed before 1980. Primarily for the reason that the Bajaus were no longer as sea-dependent as before. Bajaus today had adapted to their new environment, they no longer had to build their houses overwater that allowed them to have new forms of livelihood aside from fishing and also to do activities that do not take place on the sea. With these improvements in existing Bajau communities, the Bajaus find satisfaction in their existing communities that had influenced their rating in the sense of community index survey making the overall result relatively high.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2018